Lock-Down Effect on the Mental Health Status of Healthcare Workers During COVID-19 Pandemic - Fageera, Weam; Babtain, Fawzi; Alzahrani, Ahmad S.; Khrad, Hussain M. (Frontiers in Psychiatry, 2021)
Background: The psychological impact that outbreaks and pandemics could inflict on healthcare workers has been widely studied yet, little is known about the impact of the lockdown measures. Objectives: To assess the magnitude of depression and anxiety among healthcare professionals before and after lifting of the lockdown restrictions in Saudi Arabia. Methods: Surveys targeting healthcare workers were circulated twice: during the lockdown, and 8 weeks after lifting of lockdown. Anxiety and depressive symptoms were assessed using Generalized Anxiety Disorder (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) scales. Results: A total of 947 healthcare workers, with the mean age of (37 ± 8.9) responded to the surveys. Among these, 23-27% respondents reported clinically significant levels of anxiety and depression. Whereas, easing of the lockdown restrictions was shown to be associated with decreasing mean scores of PHQ-9 and GAD-7. The noted burden fell heavily on female workers, those with a current or a history of psychiatric disorders, suffering from chronic diseases, being in workplaces with high exposure to COVID-19 or in contact with COVID-19 patients, as well as the nurses who were living with elderly and perceived their physical and mental health as “much worse” compared to the time before the pandemic. Conclusion: Our findings identified several predictors for anxiety and depression at different time-points of the pandemic. Thus, priority to psychological support measures might be needed for these groups.